2018
DOI: 10.5530/pj.2018.3.78
|View full text |Cite
|
Sign up to set email alerts
|

The Phythochemical Research of Armenian Apricot Gums (Gummi armeniacae)

Abstract: Aim:The plant derivative, the gum's exudates are of great interest among polysaccharides. Nowadays, it is of crucial importance to study the structural peculiarities and the conditioned biological activity of the Gummi Armenicae of native origin as an alternative version of the Gummi Arabicae. Materials and methods: As a material for research served the gum procured from Apricot trees (Armenian Vulgaris Lam.), cultivated in different regions of Armenia annually in spring during juice motion period in 2010-2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Since arabinose and galactose are the most abundant monosaccharides in the PAGE composition, it is suggested that this gum has an galactoarabinan-like structure. In a recent study, Babken et al (2018) used 1 H and 13 C NMR analyses to elucidate the structure of PAGE. They found that this gum is a complex polysaccharide composed of α and β-L-Arap, α and β-D-Galp and α and β-D-glucopyranoses (β-D-Glcp).…”
Section: Chemi C Al and S Truc Tur Al Propertie Smentioning
confidence: 99%
See 4 more Smart Citations
“…Since arabinose and galactose are the most abundant monosaccharides in the PAGE composition, it is suggested that this gum has an galactoarabinan-like structure. In a recent study, Babken et al (2018) used 1 H and 13 C NMR analyses to elucidate the structure of PAGE. They found that this gum is a complex polysaccharide composed of α and β-L-Arap, α and β-D-Galp and α and β-D-glucopyranoses (β-D-Glcp).…”
Section: Chemi C Al and S Truc Tur Al Propertie Smentioning
confidence: 99%
“…Accordingly, it is clear that phenolic compound present in PAGE is strongly involved in antioxidant activity as determined by DPPH assay. Babken et al (2018) determined the phenolic profile of PAGE using GC-MS analysis. It was found that PAGE had, on average, 7.58% catechols, 4.27% hydroquinones, and 5.69% pyrogallol.…”
Section: Antioxidant Capacitymentioning
confidence: 99%
See 3 more Smart Citations